2016
DOI: 10.1016/j.humimm.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of acute rejection in hepatitis B virus positive liver transplant recipients and the impact of hepatitis B immunoglobulin

Abstract: Historically, hepatitis B virus (HBV) liver transplantation (LT) recipients have less acute cellular rejection (ACR) than those without HBV. We questioned whether this has persisted in an era of decreased Hepatitis B immunoglobulin use (HBIG) given its in vitro immunoregulatory effects. We compared the incidence, risk factors and outcomes of ACR among 40,593 primary LT recipients with HBV, hepatitis C, steatohepatitis, and immune liver disease (OPTN 2000–2011). We also assessed the in vitro effect of HBIG on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(38 reference statements)
0
5
0
1
Order By: Relevance
“…There are limited in vitro data suggesting that HBIg may inhibit alloantigen specific T cell responses, dendritic cell maturation, and cytokine production [ 35 ]. A recent study [ 37 ], albeit with lower HBIg concentrations as in prior in vitro studies [ 38 , 39 ], found no enhancing role on regulatory T cell generation. However, more in vivo and in vitro data are needed to determine the possible immunosuppressive effect of HBIg.…”
Section: Discussionmentioning
confidence: 88%
“…There are limited in vitro data suggesting that HBIg may inhibit alloantigen specific T cell responses, dendritic cell maturation, and cytokine production [ 35 ]. A recent study [ 37 ], albeit with lower HBIg concentrations as in prior in vitro studies [ 38 , 39 ], found no enhancing role on regulatory T cell generation. However, more in vivo and in vitro data are needed to determine the possible immunosuppressive effect of HBIg.…”
Section: Discussionmentioning
confidence: 88%
“…Cell tracking dyes are commonly combined with each other, with fluorescent antibodies, and/or with genetic markers to enable: (a) in vitro or in vivo tracking of phenotypically defined subsets within heterogeneous populations (e.g., [5,22]); or (b) identification and characterization of cell populations that do or do not proliferate in response to a given stimulus (e.g., [8,18,37]). The multiplicity of spectral detection options available on most digital flow cytometers means that when selecting fluorochrome combinations for such studies it is important to evaluate the impact of candidate cell tracking dye(s) on the ability to simultaneously detect other common fluorochromes.…”
Section: Methodsmentioning
confidence: 99%
“…Both dye types have also proven valuable for a wide range of in vitro studies including antigen presentation [1214], mechanism and specificity of cytotoxic effector killing [15–17] (Subheading 3.6), and regulatory T cell activity [18,19]. Infectious agents [20,21], subcellular components ( e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao i saradnici iznose zaključak da je transplantacija jetre definitivan terapeutski izbor, dok nukleozidni analozi mogu poboljšati preživljavanje kod nekih bolesnika (23). Preporuka o primeni humanog B imunoglobulina vremenom je, takođe, promenjena i suspendovana (24,25). Postoje i studije koje navode uspešnost terapijske izmene plazme u preživljavanju ovih pacijenata (26).…”
Section: Diskusijaunclassified